2002
DOI: 10.1002/art.10388
|View full text |Cite
|
Sign up to set email alerts
|

High levels of osteoprotegerin and soluble receptor activator of nuclear factor κB ligand in serum of rheumatoid arthritis patients and their normalization after anti–tumor necrosis factor α treatment

Abstract: Objective. To test the hypotheses that 1) proinflammatory cytokines affect osteoprotegerin (OPG) and soluble receptor activator of nuclear factor B ligand (sRANKL) production and therefore the OPG and sRANKL levels differ in rheumatoid arthritis (RA) patients in comparison with healthy individuals; and 2) anti-tumor necrosis factor ␣ (anti-TNF␣) therapy influences OPG and sRANKL levels.Methods. Sera were obtained from healthy individuals or RA patients receiving the combination of infliximab and methotrexate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
110
8
5

Year Published

2003
2003
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(149 citation statements)
references
References 34 publications
23
110
8
5
Order By: Relevance
“…Decoy receptors for TRAIL have been implicated as crucial anti-apoptosis mechanisms for TRAIL, although the parallel susceptibility of RA synovial cells to both TRAIL and anti-DR5 Ab suggests that this might not apply to RA synovial cells. Alternatively, the synovial levels of endogenous TRAIL apoptosis blockers, such as soluble DR4, DR5, or OPG, might be increased in RA patients (30,31). Blockade of TRAIL-mediated apoptosis with the soluble DR5 is known to increase susceptibility to the development of arthritis in mice (6).…”
Section: Discussionmentioning
confidence: 99%
“…Decoy receptors for TRAIL have been implicated as crucial anti-apoptosis mechanisms for TRAIL, although the parallel susceptibility of RA synovial cells to both TRAIL and anti-DR5 Ab suggests that this might not apply to RA synovial cells. Alternatively, the synovial levels of endogenous TRAIL apoptosis blockers, such as soluble DR4, DR5, or OPG, might be increased in RA patients (30,31). Blockade of TRAIL-mediated apoptosis with the soluble DR5 is known to increase susceptibility to the development of arthritis in mice (6).…”
Section: Discussionmentioning
confidence: 99%
“…In all experimental results of arthritis studied thus far, inhibition of RANKL completely prevented bone loss and partially protected cartilage. As for RA patients, high serum levels of soluble RANKL 58 and increased expression of RANKL mRNA in synovial tissues 59 were observed, suggesting that RANKL is the principal mediator of bone loss in human RA. As far as we know, our study is the first to clarify the high level of RANKL mRNA in human bone marrow cells from RA patients.…”
Section: Gene Expression Analysis Of Major Lineage-defining Factors Imentioning
confidence: 97%
“…52 In line with our results, Cao et al 53 suggested that the changes in RANKL expression associated with aging may contribute, at least in part, to the gradual loss of bone that occurs with age and the development of agerelated osteoporosis. However, some studies found no age-dependent change in the RANKL serum level in healthy individuals 54 or decreased in the serum RANKL concentration with age. 55 One explanation for this discrepancy may be that serum RANKL levels do not consistently reflect the local microenvironment in the bone.…”
Section: Gene Expression Analysis Of Major Lineage-defining Factors Imentioning
confidence: 99%
“…RA patients exhibit high serum levels of OPG and soluble RANKL, which normalize after anti-TNF␣ treatment (55). RANKL mRNA is present in the synovial lining layer in patients with RA (56), and RANKL as well as RANK are also detected in the synovium of rats with collagen-induced arthritis (3).…”
Section: Rank/rankl/opg and Ramentioning
confidence: 99%